Lack of NG2 exacerbates neurological outcome and modulates glial responses after traumatic brain injury. Issue 4 (6th December 2015) - Huang, Changsheng; Sakry, Dominik; Menzel, Lutz; Dangel, Larissa; Sebastiani, Anne; Krämer, Tobias; Karram, Khalad; Engelhard, Kristin; Trotter, Jacqueline; Schäfer, Michael K.E.
Abstract : Traumatic brain injury (TBI) is a major cause of death and disability. The underlying pathophysiology is characterized by secondary processes including neuronal death and gliosis. To elucidate the role of the NG2 proteoglycan we investigated the response of NG2‐knockout mice (NG2‐KO) to TBI. Seven days after TBI behavioral analysis, brain damage volumetry and assessment of blood brain barrier integrity demonstrated an exacerbated response of NG2‐KO compared to wild‐type (WT) mice. Reactive astrocytes and expression of the reactive astrocyte and neurotoxicity marker Lcn2 (Lipocalin‐2) were increased in the perilesional brain tissue of NG2‐KO mice. In addition, microglia/macrophages with activated morphology were increased in number and mRNA expression of the M2 marker Arg1 (Arginase 1) was enhanced in NG2‐KO mice. While TBI‐induced expression of pro‐inflammatory cytokine genes was unchanged between genotypes, PCR array screening revealed a marked TBI‐induced up‐regulation of the C‐X‐C motif chemokine 13 gene Cxcl13 in NG2‐KO mice. CXCL13, known to attract immune cells to the inflamed brain, was expressed by activated perilesional microglia/macrophages seven days after TBI. Thirty days after TBI, NG2‐KO mice still exhibited more pronounced neurological deficits than WT mice, up‐regulation of Cxcl13, enhanced CD45+ leukocyte infiltration and a relative increase of activated Iba‐1+/CD45+ microglia/macrophages. Our study demonstrates that lack of NG2 exacerbates the neurological outcome after TBI and associates with abnormal activation of astrocytes, microglia/macrophages and increased leukocyte recruitment to the injured brain. These findings suggest that NG2 may counteract neurological deficits and adverse glial responses in TBI. GLIA 2016;64:507–523 Main points: NG2‐KO mice show exacerbated neurological outcome and abnormal glial responses after TBI. The leukocyte‐recruiting immunomodulatory CXCL13 is specifically up‐regulated in activated microglia/macrophages of NG2‐KO mice. NG2 modulates glial responses.